CONTRIBUTIONS OF THE PILATES METHOD OF SELF-CONCEPT IN PEOPLE WITH VISUAL DISABILITY: CASE REPORT. (Fiep Bulletin - online, 2013)
The survey, developed as a case report, aimed to implement and evaluate the contribution of the Pilates method of self-concept in people with visual disability. He was part of a search women with disabilities, from low vision, no practitioner of physical activity. We performed 10 sessions of Pilates, twice a week, with duration of 60 minutes. Before and after the development of the program of Pilates, was applied to FSS: Factor Scale of Self-concept (Tamayo, 1981). Information obtained in data collection have found that there were significant and positive changes in the student's self-concept in relation to self-control, social responsiveness, social attitude and self somatic.
Keywords: Pilates; self-concept; visually disability